(3fJGFL GdCacGQ aj JNQjL CMGOjK GdGPcGQs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeMehO HLejd GdCPcGQ CeG HYO abO YReJ Ydi JNQjL GdCMGOjK GdePchQI ai cJGH GdCPcGQ s
(3BNQgG (B:s
(3JNQjL MOjK ef bQC BjI GdcQSi hChd ee GdeDef YUe Pdc Gdjhe ef cd TF s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3QhGjI eMeO Hf eMeO Hf eMeO GdcQci SfI (B837s
(3fbdJ Yf fSNI efbhdg Yf fSNI ajgG NW GdeSfa s
(3HChdg YOI JedcGJ s
(3bQf GdfSN (B:s
Keywords: (3GdMOjK h GdeUWdMs